The forms of occurrence and geochemistry of sulfides in hard coal deposits of the Libiąż Beds in the Upper Silesian Coal Basin, Southern Poland - Bielowicz, Barbara; Misiak, Jacek (Geology, Geophysics and Environment, 2018)
Samples of coal from the eastern part of the Upper Silesian Coal Basin, between Jaworzno and Libiąż, were collected from test boreholes and underground excavations in the Janina Coal Mine, southwest Poland. The No. 111-119 hard coal seams are in the upper part of the Cracow Sandstone Series (the Libiąż Beds, Westphalian D). Macroscopically, iron sulfides (pyrite and marcasite) found in hard coal seams are usually in vein and impregnation forms. On the basis of microscopic observations, the following forms of iron sulfides occurrence in the studied coal were observed: framboidal pyrite, euhedral crystals, skeletal and massive vein forms, or pocket-like (impregnation) forms. On the basis of SEM-EDS analysis and X-ray diffraction it can be stated that the iron sulfides observed in coal are a mixture of pyrite and marcasite. WDS analysis in the micro area revealed the chemical composition of sulfides. The iron sulfides contain admixtures of Pb, Hg, Zn, Cu, Au, Ag, Sb, Co, and Ni. There was no As and Cd found in the examined minerals. It has been shown that the tested iron sulfides do not include significant admixtures. There is only a slight enrichment in lead in the vein forms of sulfides. In addition to the iron sulfides, individual inclusions of galena and sphalerite within the pyrite and marcasite have been observed.